The Negation of the Exile in the Messianic Doctrine of the Karaite Mourners of Zion - Erder, Yoram 1952- (1998)
The Karaite Mourners of Zion owe much of their messianic doctrine to the Qumran literature. It is not only in terms of its content that the messianic doctrine of the Karaites is similar to that of Qumran, but also the Qumran Pesher, the means by which the Qumran sect developed its messianic doctrine, was used by the Karaite Mourners of Zion. Therefore, their main messianic doctrine is spread throughout their commentaries on the Bible, particularly those of the books of Prophets, Psalms, the Song of Songs and the book of Daniel. It is beyond the scope of this paper to give a full detailed description of the messianic doctrine of the Mourners of Zion, but rather to present their view of the complete and utter negation of Jewish existence in the Diaspora. We shall go on to present the values of the ideal society as depicted by the Mourners of Zion. The presentation of such a society, one so different from the Jewish society in the Diaspora as portrayed by their writings, comes to illustrate their criticism of the Exile. Salvation will not be fulfilled without the repentance of the nation. Repentance includes two interlinked elements, mourning for Zion and migration to Palestine. Concerning the ideal society as envisioned by the Mourners of Zion; besides the utter elimination of the Exile, they anticipated the establishment of a Kingdom ruled by the house of David, the erection of the Temple, the restoring of the leadership to the priests, and the revival of the Hebrew language. The mourners of Zion fiercely criticized the Rabbanites who became rich in the Diaspora as a result of their commercial enterprises. Once the people will return to its land, mourning and asceticism should be abandoned, but there is, however, one economic principle to which the Mourners of Zion remained faithful, opposition to an economy based upon commerce and trade. Trade may become a factor likely to corrupt society even in the land of Israel, just as it had done in exile. Finally, a distinction is made between Karaism and modern Zionism.